Filterisasi Air Bersih dan Penyelamatan Sumber Mata Air di Desa Mulyoasri, Kecamatan Ampelgading, Kabupaten Malang - Husain Latuconsina; Eva Seda Gadi; Ahmad Isomudin; Heksni Laksa Berlian; Zahid Ubaidillah; Putri Nur Azizah; Ainul Yaqin; Fendri Yuwasahin; Tri Adi Handoyo Putra; Vara Arsyilia Fitriani; Muhammad Alhayyu Infant (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Water is a basic need of human life for drinking, cooking, washing, agricultural activities, plantations, animal husbandry, and various other daily activities. The purpose of implementing the Field Work Lecture Activities-Community Empowerment (KKN-PPM) of Thematic of the University of Islam Malang is to empower the village community in their efforts to utilize clean water and save of springs. KKN-PPM of Thematic activities are carried out for 1 month (1 February‒1 March 2020). One of the problems faced by the community is the difficulty of getting clean water. During the rainy season, the water is dark brown in color, caused by mud material blocking the springs, and made worse by the water becomes cloudy due to a water filtration system that is not yet available and does not have a water reservoir. Based on these problems, the students of KKN-PPM of Thematic carried out an empowerment program with the theme clean water filtration and efforts to save springs. Community empowerment activities related to clean water are carried out through four stages, namely: 1) Location survey and public consultation; 2) Household-scale clean water filtering, and socialization of the use of clean water filtering to the community; 3) Counseling and actions to protect springs; and 4) Evaluation of activities through pre-test and post-test to the community. The results obtained from activities the KKN-PPM of thematic are that the community in the Mulyoasri village positively welcomes the program by understanding how to make filtering equipment and assessing that it is efficient and effective enough to produce clean water. The community also gains understanding and is committed to jointly protecting springs.